(untitled) (Research, Society and Development, 2025)
This article describes a solution for monitoring, automation, and control in industrial production. The presented approach combines Internet of Things (IoT), cloud storage, and sensing technologies applied to a cheese manufacturing tank. The sensors attached to the cheese manufacturing tank enable readings of temperature, pH, and level, contributing to process control, streamlining decision-making, and consequently improving product quality. The system can be accessed via the internet, allowing remote access and control, where users select the type of cheese to be produced, and based on the algorithm, the tank autonomously performs the process. The results demonstrate that through the digitization process, it is possible to monitor and act upon the tank, either manually or through autonomous programming, using a multi-technology interface of open-source circuits and code, providing a low investment compared to proprietary solutions in the industrial market. In this present work, in addition to controlling and digitizing equipment data that directly affects profitability, the benefits of the implemented system extend to increased productivity, remote access, cloud storage, and the possibility of adapting industrial equipment (retrofitting) from different scenario segments, which were configured within a framework.